Microscopic and macroscopic analysis for TPS SiC material under Earth and Mars re-entry conditions. (24th September 2012) - Vérant, J-L.; Perron, N.; Balat-Pichelin, M.; Chazot, O.; Kolesnikov, A.; Sakharov, V.; Gerasimova, O.; Omaly, P.
This paper deals with gas/surface interaction processes occurring during the re-entry phase of a vehicle into atmosphere. In the framework of a two-year INTAS/CNES project under ONERA management (France), scientific investigations were driven by six research laboratories: PROMES-CNRS (France), VKI (Belgium), IPM (Russia), NIIMech-MSU (Russia), USU (Russia) and ONERA to enhance the knowledge of catalycity phenomena on thermal protection systems material with regard to microscopic and macroscopic point of view. The first year was devoted to air gas surface processes according to Pre-X vehicle chosen trajectory conditions whenever the second year was devoted to CO2 gas according to aerocapture Orbiter Mars PREMIER chosen conditions.